AN ANALYSIS OF DEIXIS IN ENGLISH TEXTBOOKS DIALOGUE FOR CLASS VII - Jauhar Helmie; Vina Nurviyani; Neng Asti Nurul Awaliyah (Universitas Suryakancana, 2026)
ABSTRACTThis research paper explores the use of deixis in the English language, specifically focusing on the analysis of deixis found in English Textbooks Dialogue for Class VII students in Indonesia. The study is motivated by the need to understand the historical context of deixis and its practical implications for future linguistic research. The researcher employed a qualitative method to analyze dialogues from chapters 1 to 3 of the textbook